Evaluating the effect of oral clarithromycin on acute cutaneous leishmaniasis lesions compared with systemic glucantime. (3rd April 2022) - Zabolinejad, Naghmeh; Layegh, Pouran; Abbasi Shaye, Zahra; Salehi, Maryam; Ghanizadeh, Somayeh
Abstract: Background and aim: It is widely accepted that the high prevalence of leishmaniasis, demands the search for a tolerable effective treatment with the least side effects. This study aimed to evaluate the effect of treatment with clarithromycin on regression of lesions. Materials and methods: This study was performed on 20 patients with leishmaniasis referred to dermatology clinic in 2017–2018. They were divided into two groups of intervention (500 mg oral clarithromycin twice a day) and control (20 mg/kg/day systematic glucantime). Induration size of lesions was recorded. Results: We had 20 patients with acute cutaneous leishmaniasis (CL) with 45 lesions in the control group and 49 lesions in the intervention group. In the control group, the mean number of lesions was 3 ± 2.8 and 5 ± 4.3 in each person in the control and intervention group ( p =.63). The mean size of the largest diameter of lesions' induration at the beginning of the treatment was 19.81 ± 13 and 15.47 ± 15.6 mm in control and intervention group ( p =.3) which changed to 1.59 and 0 respectively in three months after the treatment ( p =.001). Conclusions: We concluded oral clarithromycin had therapeutic effects on acute CL similar to systematic glucantime and could be considered as a safe and effective treatment option.